Angiotensin receptor blockers versus angiotensin‐converting enzyme inhibitors: Longitudinal associations with PET amyloid in the Alzheimer's Disease Neuroimaging Initiative: Neuroimaging / evaluating treatments. (7th December 2020) - Ouk, Michael; Wu, Che‐Yuan; Rabin, Jennifer S.; Edwards, Jodi D.; Ramirez, Joel; Masellis, Mario; Swartz, Richard H.; Herrmann, Nathan; Lanctot, Krista L.; Black, Sandra E.; Swardfager, Walter
Abstract: Background: Evidence suggests that Angiotensin II type‐1 Receptor Blockers (ARBs) and Angiotensin‐Converting Enzyme Inhibitors (ACE‐Is) may be differentially beneficial for cognition, but there is little clinical evidence supporting possible mechanisms. This study examines longitudinal associations between the use of ARBs and ACE‐Is with summary cortical and subregional brain amyloid‐β (Aβ). Method: This study included participants with hypertension who were using an ACE‐I or ARB with available PET data from the Alzheimer's Disease Neuroimaging Initiative (ADNI) 1, GO, and 2 databases (years 2010‐2018). Analyses were conducted in subgroups with normal cognition (NC) and with cognitive impairment (amnestic mild cognitive impairment or Alzheimer's disease [AD/MCI]). The outcome was PET Aβ SUVR in a cortical summary region and subregions involved in early/late stages of Aβ accumulation. Linear mixed‐effects models with inverse probability of treatment weighting were used to compare rates of Aβ accumulation over 48 months between ARB and ACE‐I users. Models were adjusted for demographics, ApoE ε4 status, baseline MMSE, relevant comorbidities, and other concurrent antihypertensive use. Result: In the NC group (n=124, age=74.8±5.6, 46.3% women), ARB vs. ACE‐I use was associated with a slower rate of Aβ accumulation in the cortex (β=‐0.138 [‐0.062, ‐0.223]), the inferior temporal lobe (β=‐0.165 [‐0.076, ‐0.255]), and precuneus (β=‐0.164 [‐0.075, ‐0.252]). In people with AD/MCI (n=246, age=74.5±7.3, 39.1% women), users of an ARB vs. an ACE‐I did not differ in the rate of Aβ accumulation in the cortex (β=0.019 [‐0.038, 0.075]), in the above regions (inferior temporal lobe β=‐0.027 [‐0.102, 0.048]; precuneus β=0.008 [‐0.051, 0.067]), or in areas associated with later Aβ accumulation (parietal lobes β=0.035 [‐0.027, 0.097]; frontal lobes β=0.014 [‐0.053, 0.081]). Conclusion: In cognitively‐normal adults, ARB use was associated with a significantly slower rate of Aβ accumulation. This difference may be partially explained by preservation of Aβ‐clearing effects of the angiotensin‐converting enzyme by ARBs. In contrast, there were no significant differences in AD/MCI which could reflect both plateau effects, less impact on more advanced stages, or a relatively small sample size. Prospective analyses and clinical trial evidence are warranted to confirm the potential benefit of ARB use to slow Aβ accumulation and prevent cognitive impairment.